2003
DOI: 10.1128/iai.71.10.5951-5961.2003
|View full text |Cite
|
Sign up to set email alerts
|

Entry and Intracellular Replication ofEscherichia coliK1 in Macrophages Require Expression of Outer Membrane Protein A

Abstract: Interactions between Escherichia coli K1, which causes meningitis in neonates, and macrophages have not been explored well. In this study we found that E. coli K1 was able to enter, survive, and replicate intracellularly in both murine and human macrophage cell lines, as well as in monocytes and macrophages of newborn rats. In addition, we demonstrated that OmpA ؉ E. coli also enters and replicates in human peripheral blood monocytes in vitro. Outer membrane protein A (OmpA) expression on E. coli contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 42 publications
6
111
0
2
Order By: Relevance
“…Properties vary between bacteria (16). It is not clear what role OmpA plays in invasion and survival within cells; it may depend on the context, because OmpA-deficient bacteria have been reported to survive better in macrophages (25) and it has been shown that neutrophil elastase can attack OmpA (26). However, OmpA has been shown to be required for interaction and for crossing the brain microvascular endothelial cell barrier (27,28), and OmpA may reduce complement-mediated attack (29).…”
Section: Discussionmentioning
confidence: 99%
“…Properties vary between bacteria (16). It is not clear what role OmpA plays in invasion and survival within cells; it may depend on the context, because OmpA-deficient bacteria have been reported to survive better in macrophages (25) and it has been shown that neutrophil elastase can attack OmpA (26). However, OmpA has been shown to be required for interaction and for crossing the brain microvascular endothelial cell barrier (27,28), and OmpA may reduce complement-mediated attack (29).…”
Section: Discussionmentioning
confidence: 99%
“…Neonates having lower than the threshold levels of C4bp may be at a higher risk to E. coli K1 meningitis as evidenced when the bacterium treated with adult serum, which contained higher amounts of C4bp, could not invade HBMEC compared with newborn serum treatment (18). Nonetheless, neither of the sera prevents the entry of E. coli K1 into macrophages or dendritic cells (DCs) for which OmpA expression is also needed, indicating that various epitopes of OmpA are involved at different stages of pathogenesis of E. coli K1 meningitis (19,20). Therefore, in this study it is our goal to delineate the roles of different domains of OmpA interacting with various cells in vitro and their role in a well established newborn mouse model of meningitis (7,(21)(22)(23).…”
mentioning
confidence: 99%
“…Studies have shown that a high degree of bacteremia is required for E. coli to cross the blood-brain barrier, indicating that the bacterium must evade host defense mechanisms and survive in the blood stream (6,7). Our studies in the newborn rat model of hematogenous meningitis have demonstrated that E. coli enters monocytes and macrophages and then multiplies in a time-dependent fashion (8). Therefore, the ability of E. coli to survive in host immune cells like monocytes, macrophages, and neutrophils may represent an important step in the vicious cycle of this organism.…”
mentioning
confidence: 88%